Carotid artery stenting in JAK2 V617F-positive essential thrombocythemia with symptomatic internal carotid artery stenosis: a case report - Du, Minghui; Hu, Yinbao; Liang, Zhigang (Frontiers in Cardiovascular Medicine, 2025)
Essential thrombocythemia (ET) is a myeloproliferative neoplasm (MPN) characterized by abnormal megakaryocyte proliferation and a markedly elevated platelet count, which predisposes patients to thrombotic or hemorrhagic events. Approximately 50%–60% of ET patients harbor a JAK2 V617F mutation. This mutation drives constitutive JAK kinase activation, promoting megakaryocyte proliferation and platelet production, while potentially activating inflammatory pathways and damaging vascular endothelium. We report a case of a JAK2 V617F-positive ET patient (sporadic presentation) who successfully underwent carotid artery stenting (CAS) for symptomatic internal carotid artery (ICA) stenosis. A 66-year-old male with known JAK2 V617F-positive ET presented with transient slurred speech and right-sided facial droop with mouth deviation. Magnetic resonance imaging/magnetic resonance angiography (MRI/MRA) revealed an acute cerebral infarction in the right basal ganglia and corona radiata, along with right ICA stenosis. Aggressive perioperative platelet and inflammation control, employing hydroxyurea, aspirin, and ticagrelor, was instrumental in mitigating the heightened thrombosis risk associated with the JAK2 V617F mutation. This case underscores that ET patients with the JAK2 V617F mutation face a substantial risk of thrombotic recurrence. It highlights the critical importance of rigorous preoperative platelet control, personalized antiplatelet therapy guided by pharmacogenomic principles, and multidisciplinary management in high-risk ET patients undergoing CAS.